The Economics of Duty-Free Shopping - Vidar Christiansen; Stephen Smith (Center for Economic Studies and ifo Institute (CESifo), 2001)
In 1999 the EU abolished duty-free on intra-EU travel, whilst other countries still retain duty-free shopping for international travellers. We address several aspects of duty-free trade, including effects on consumption, revenue and price-setting. From a global perspective we identify the distortions generated by duty-free trade. We review, and dismiss, various arguments that might conceivably support a role for duty-free in promoting global economic welfare. The existence of duty-free trade is explained as a phenomenon that individual countries find in their national self interest as seen both from the arrival and the departure end, i.e. countries have reasons both to admit duty-free goods and to permit their sale to departing passengers.
Keywords: H00; 330